A steganographic method of embedding an identifier into the spatial data of an electronic map - Blinova, Evgenia A.; Stashevskaya, Irina Yu.; Urbanovich, Pavel P. (Journal of the Belarusian State University. Mathematics and Informatics, 2023)
Electronic maps (e-maps), which are a set of computer files, are the main form of representation of geographic information to the end user. An important task is protecting e-maps from unauthorised use or modification. This paper describes the steganographic method of embedding an invisible digital watermark into the spatial data of e-maps for protecting copyright, ensuring integrity of maps or proving their authenticity. The method is applicable to e-maps in the Shapefile and GeoJSON formats. It is based on the placement of additional points in spatial objects (polygons) of the e-map. In this case the e-map is used as a carrier object, and point coordinates are elements of the key information of the steganographic transformation. This establishes a relationship between the spatial objects of the e-map, which ensures their integrity. Algorithms for direct and inverse steganographic transformations are considered. The developed StegoMap Internet service for implementing the placement and extraction of an invisible digital watermark on the basis of the proposed method is described.